Effect of phosphates on early-age hydration process and products of calcium aluminate cement at −10 °C. (5th September 2022) - Li, Zhiyuan; Tian, Bo; Li, Lihui; Quan, Lei; Li, Dafu
Highlights: The effect of different phosphates on the setting behavior of CAC at −10℃ was analyzed. The mechanism of sodium pyrophosphate modification of CAC was described. New crystal products of phosphate-modified CAC were found. A kind of cement system which can set and harden well at negative temperature is presented. Abstract: Phosphates can effectively enhance the hydration rate of calcium aluminate cement (CAC). In order to explore the application potential of phosphates modified CAC at negative temperature, this study investigates the hardening and hydration characteristics of CAC modified with four kinds of sodium phosphates (Na3 PO4, Na4 P2 O7, Na5 P3 O10, and ((NaPO3 )n ) at −10 ℃. Among those four different systems, the mechanism of the CAC modified by Na4 P2 O7 with the best setting and mechanical performance is discussed. The results indicates that, the increase of the content of Na4 P2 O7 increases the production of canaphite (CaNa2 P2 O7 ·4H2 O) at the early stage of hydration which makes the paste harden and set more rapidly at −10 ℃. However, in the following hydration process the content of CAH10 decreases, resulting in the loose and defective microstructure, and the insufficient compressive strength development. The CAP2 system with 10% Na4 P2 O7 content has good setting performance and strength development. The final setting time of cement is 130 min, and the compressive strength of cement reaches 47 MPa at 7d.